A new model of temporary focal neocortical ischemia in the rat. - Buchan, A; Xue, D; Slivka, A (1992)
BACKGROUND AND PURPOSE: We describe a new rat model of temporary focal ischemia that produces neocortical ischemia without the need for prolonged anesthesia. METHODS: Temporary focal cerebral ischemia was initiated during halothane anesthesia, maintained for varying periods without anesthesia, and reversed by clip removal requiring brief anesthesia. Tandem carotid and middle cerebral artery occlusion for 1-4 hours and permanent occlusion were used to determine the duration and extent of ischemia necessary to produce predictable volumes of neocortical infarction in Wistar and spontaneously hypertensive rats. RESULTS: In Wistar rats, occlusion of the right middle cerebral and both common carotid arteries resulted in cerebral blood flow reductions to approximately 8% of baseline. One hour of transient ischemia with 23 hours of reperfusion did not result in infarction. Three hours of ischemia followed by 21 hours of reperfusion resulted in infarction comparable to that caused by 24 hours of permanent ischemia. In spontaneously hypertensive rats, unilateral right middle cerebral and common carotid artery occlusion reduced cerebral blood flow to approximately 11% of baseline. Minimal damage was seen with 1 hour of reversible ischemia, but intervals of 2 and subsequently 3 hours followed by 22-21 hours of reperfusion produced progressively larger infarcts. Damage indistinguishable from that seen with 24 hours of permanent ischemia was seen with 3 or 4 hours of transient ischemia followed by 21 or 20 hours of reperfusion. CONCLUSIONS: For unanesthetized normothermic rats, cerebral blood flow reductions to 10-20% of baseline resulted in maximal infarction once ischemic durations exceeded 2-3 hours. To be effective, experimental therapies aimed at lessening infarct size or restoring blood flow must be initiated within this critical time interval.